Childhood, family, and sociocultural change in India: reinterpreting the inner world - Sharma, Dinesh (Oxford Univ. Press, 2003)
Contributed articles on child development, psychoanalysis, and culture in Indian society based on the works of Sudhir Kakar; also includes a short interview with the Indian psychoanalyst.